The Effect of Training on Employee Performance - Muhammad Zacky Syauqy Ibnu Shodiq; Mutiara Fitridiani; Shelly Brilliant; Stephanie Dwi Wahyuning Tyas; Titin Suhartini (PT. Keberlanjutan Strategis Indonesia, 2026)
The increasing competition in the business environment requires organizations to improve employee performance to achieve organizational goals. One of the key strategies in Human Resource Management is training, which aims to enhance employees knowledge, skills, and abilities. This study aims to examine the effect of training on employee performance. This research employs a quantitative explanatory approach with data collected from 100 employees. Data were gathered using a structured questionnaire measured on a five-point Likert scale. The analysis techniques included validity and reliability tests, classical assumption testing, simple linear regression, t-test, and coefficient of determination (R²). The results show that training has a positive and significant effect on employee performance, with a regression coefficient of 0.612 and a significance value of 0.000 (< 0.05). The coefficient of determination indicates that training explains 41.2% of employee performance, while the remaining 58.8% is influenced by other factors. These findings suggest that effective training programs play an important role in improving employee performance